Early Mesozoic tectonic transition of the eastern South China Block: constraints from Late Triassic Dashuang complex in eastern Zhejiang Province. Issue 8 (24th May 2019) - Xu, Xianbing; Li, Qiming; Gui, Lin; Su, Yuping; Zhang, Xuefen
ABSTRACT: The Mesozoic tectonic transition from the Palaeo-Tethys tectonic regime to the Palaeo-Pacific tectonic regime in the eastern South China Block has long been debated. Geochemical and zircon U–Pb–Hf isotopic studies were conducted on the Dashuang complex in the eastern Zhejiang Province. The Dashuang complex consists mainly of quartz syenite in the northwestern part and quartz monzonite in the southeastern part. New laser ablation inductively coupled plasma mass spectrometry zircon U–Pb data show that the quartz syenite, the quartz monzonite, and its chilled margin (fine-grained granite) crystallized at 235 ± 4 Ma, 232 ± 3 Ma, and 230 ± 1 Ma, respectively. The Dashuang complex intrudes into the Chencai Group gneiss that postdated ~646 Ma and underwent anatexis at 443 ± 14 Ma. The quartz monzonite shows A-type granite affinity, characterized by high K2 O + Na2 O and Zr + Nb + Ce + Y, high FeOT /(MgO + FeOT ) and Ga/Al ratios, an enrichment in light rare earth elements, and depletions in Ba, Sr, and Eu. The quartz monzonite has zircon εHf ( t ) values of −14.2 to –11.9 and two-stage model ages of 1788–1922 Ma. Zircon εHf ( t ) values of the chilled margin (fine-grained granite) and wall rock (gneiss) are scattered (−18.2 to –6.3 and −19.5 to 10.2). The corresponding two-stage model ages are 1482–2133 Ma and 1184–2471 Ma, respectively. The Dashuang complex was derived mainly from partial melting of Neoproterozoic clastic rocks in the Cathaysia Block. Geochemical data indicate that the quartz monzonite formed in a post-collision extensional environment. These results, considered with previous data, indicate that the transition from the Palaeo-Tethys to the Palaeo-Pacific tectonic regimes of the eastern South China Block occurred during the Late Triassic (225–215 Ma).